Identification of Grape NRT Gene Family and Analysis of Its Expression in Leaves Under Nitrogen-Deficiency Stress - Zhongyi Yang; Junjie Mei; Wei Zheng; Falak Sher Khan; Mohammad Nasim Bhuiyan; Kangjie Wang; Mohammad Saidur Rhaman; Naomi Abe-Kanoh; Wei Ji (Horticulturae)
Nitrogen, an indispensable macronutrient, significantly affects the appearance, quality, and yield of grapes (Vitis vinifera). Adequate nitrate uptake and intracellular transport, facilitated primarily by nitrate transport (NRT) proteins, are crucial for maintaining nutritional balance. However, there are no reports on the NRT gene family in grapes. In this study, we identified 53 Nitrate Transporter 1/Peptide Transporter Family (NPF), 3 nitrate transporter 2 family (NRT2), and 1 Nitrate Assimilation-Related 2 (NAR2) genes in the grapevine Pinot Noir PN40024 genome. A comprehensive analysis of these gene families, including their physicochemical properties, structural organization, chromosomal distribution, collinearity, cis-acting element distribution, and phylogenetic relationships, revealed the rich diversity and evolutionary conservation of the grapevine Nitrate Transporter (NRT) genes. Furthermore, the expression profiles of VvNRTs in different tissues demonstrated that the NRT genes possess spatio-temporal expression specificity. The expression patterns of the NRT genes were examined by transcriptome sequencing in grapevines across various tissues under nitrogen-deficiency conditions. The expression patterns in grapevine leaves under nitrogen-deficiency conditions showed upregulation of the VvNPF2.3 gene in conditions of nitrogen deficiency. This upregulation was strongly associated with a 62.2% reduction in indole-3-acetic acid (IAA) levels and a 21.3% increase in hydrogen peroxide (H2O2) levels, suggesting a complex regulatory response to nitrogen-induced stress. These findings emphasize the potential involvement of NRT genes in the adaptive reaction to nitrogen deficiency and set the stage for future investigations into the molecular mechanisms of nitrogen transportation in grapevines.